Saving lives by ventilating two patients with specific pressure-controlled ventilation from a single ICU-ventilator during the COVID-19 pandemic - Hureau, Maxence; Versyck, Maaike; Fontainre, Sylvie; Lambiotte, Fabien; El Beki, Nabil; Saint Leger, Piehr (Anestezjologia Intensywna Terapia, 2021)
In late December 2019, SARS-CoV-2 was discovered, which is responsible for a new human disease called COVID-19. Among all laboratory-confirmed COVID-19 cases, 14% were hospitalized, with 2% admitted to intensive care units (ICU) with acute respiratory distress syndrome (ARDS) requiring mechanical ventilation [1]. SARS-CoV-2 has spread quickly across the world, with more than one hundred million confirmed cases and more than 2,500,000 dead. In March 2020, the Hospital of Valenciennes had to admit hundreds of COVID-19 patients, and its capacity was almost exceeded [2]. More recently, in France, thousands of critically ill patients had to be admitted to ICUs. In Europe, the next wave of COVID-19 pandemic could be more severe than the first one, and we already know that, in the case of increasing numbers of critically ill, some of them will die as a result of the unavailability of mechanical ventilators [3]. This shortage may be lessened if one ventilator could service more than one patient. The main worry is that this concept could be not useful and systematically deleterious for the patient. Some concepts have already been proposed to ventilate differently two circuits with a single ventilator, with several limitations like the lack of individualization of ventilation of each circuit [4–6]. More recently, in the face of the COVID-19 pandemic, Clarke et al. [7] described a new concept able to deliver specific ventilation for two different lung tests with a single ventilator. Again, Levin et al. [8] have recently shown that a similar concept of differential ventilation using a single ventilator with flow control valves is feasible in humans.